Reading the tea leaves on China's exchange rate - Orlik, Thomas (Ft Press delivers digital shorts., 2011)
If you liked this Short, you might also like Understanding China's Economic Indicators: Translating the Data into Investment Opportunities (9780132620192) by Thomas M. Orlik. Available in print and digital formats. Predicting the appreciation of the Chinese yuan--and its powerful impact on exporters, importers, and currency markets. How much will the yuan appreciate next year? The answer will reverberate around global financial markets. For Chinese firms, the pace of appreciation is a key determinant of profitability. Exporters, like the small factories that line the coast of Guangdong province, suffer as a more expensive yuan cuts their competitive advantage. Importers, on the other hand, benefit. For currency markets...